Pengaruh Jumlah Wisatawan dan Jumlah Obyek Wisata terhadap Pendapatan Asli Daerah Kabupaten Sumenep Tahun 2015-2022 - Erliyaton, Nelli; Heru Pranjoto, R. Gatot; Samsuki (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This research aims to determine the effect of the number of tourists and the number of tourist attractions on the local revenue (PAD) of Sumenep Regency for the 2015-2022 period. The type of research used is quantitative and secondary data. The population of this study is all data on the number of tourists, tourist attractions and local revenue (PAD) from the 2015-2022 period. The sample for this research is annual data on the number of tourists, number of tourist attractions and local income for Sumenep Regency for 2015-2022. The method used in sampling this research is the saturated sample method. Data collection in this research used documentation techniques. Data were analyzed using multiple linear regression analysis methods. This research obtained results that the number of tourists did not have a significant effect on local original income in 2015-2022, the number of tourist attractions had a positive and significant effect on local original income in 2015-2022, and the number of tourists and the number of tourist attractions did not have a simultaneous effect on local original income. Sumenep Regency 2015-2022.